698. Contemporary Clinical Epidemiology of Pediatric Shigella and Campylobacter Infections in Houston, TX, 2019 and 2020. (4th December 2021) - tabarani, christy; Flores, Anthony R; Flores, Anthony R; Arias, Cesar A; Wanger, Audrey
Abstract: Background: Infections due to Gram-negative, diarrheal pathogens are a significant cause of morbidity in children. Clinical features of pediatric Shigella and Campylobacter infections in urban cities in the United States are not well described. Methods: We used a retrospective chart review of records (0-18 years of age) from a network of hospitals in Houston, TX. Only patients with Shigella spp. or Campylobacter spp. isolated from clinical samples in 2019 and 2020 were included. Demographic, clinical, and microbiological data were extracted from the medical record. Results: We identified a total of 59 and 16 pediatric patients with Shigella spp. and Campylobacter spp. infections, respectively. Hospital admission occurred in 27.1% (16/59) of Shigella and 25% (4/16) of Campylobacter. Length of stay ranged between 1 and 2 days for both pathogens (Table 1). Of cases with available clinical data, Shigella infections were more likely to report fever during their illness compared to Campylobacter (80% versus 45.4%) (Table 2). Seizures were observed in 4 Shigella infected patients. No episodes of Shigella or Campylobacter bacteremia were identified. Among patients with an identified exposure, daycare attendance and contact with individuals experiencing similar symptoms were most common (Table 2). The vast majority of Shigella species were S. sonnei (96.6%) and all Campylobacter were C. jejuni (Table 3). Resistance to trimethoprim-sulfamethoxazole (TMP-SMX) was common (40/55, 72.7%) among Shigella isolates tested. No resistance to fluoroquinolones or third generation cephalosporins in any of the Shigella spp. isolates was observed. Susceptibility testing was not performed in Campylobacter due to lack of isolates. The most frequent antibiotic used was azithromycin (in 73.3% and 75% of patients with Shigella and Campylobacter, respectively). Major complications included urinary tract infection (n=1), rectal prolapse (n=1) and splenomegaly (n=1). Conclusion: Infections due to Shigella and Campylobacter were a significant burden among pediatric patients between 2019 and 2020 in Houston, TX. The observed high frequency of resistance to TMP-SMX and emergence of multi-drug resistant Shigella in other countries warrants continued surveillance. Disclosures: Anthony R. Flores, MD, MPH, PhD, Nothing to disclose Cesar A. Arias, M.D., MSc, Ph.D., FIDSA, Entasis Therapeutics (Grant/Research Support)MeMed Diagnostics (Grant/Research Support)Merk (Grant/Research Support)